1958
DOI: 10.5558/tfc34159-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Important Insects Affecting the Spruce-Fir Forest in the Maritime Provinces

Abstract: After graduating from tlze Faculty o f Forestry, University of New Brunswick, in 1938, R. Franklin Morris was awarded a special scholarship by the Canadian Pulp and Paper Association for post-graduate studies in entomology. He received his M . Sc. from Syracuse in I940 and Ph. D. from the Universio of Michigan in I947. His present work, and interests, are concerned almost entirely with basic research in the population dynamics of forest insects and other organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1968
1968
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…A study of the predation by tits during the outbreak of winter moth in Wytham in 1948 revealed that only 2-5% of the caterpillars were taken (Betts 1955, Varley andGradwell 1962a) . There is substantial evidence in the literature for the inability of bird predators to prevent insect outbreaks (e.g., Morris 1958, Clark 1964.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the predation by tits during the outbreak of winter moth in Wytham in 1948 revealed that only 2-5% of the caterpillars were taken (Betts 1955, Varley andGradwell 1962a) . There is substantial evidence in the literature for the inability of bird predators to prevent insect outbreaks (e.g., Morris 1958, Clark 1964.…”
Section: Introductionmentioning
confidence: 99%
“…A I acre site is simulated in the model but infestations of blackheaded budworm may extend over much larger areas (Morris 1958). This is a valid criticism; however, a sensitivity analysis of the model showed that its basic qualitative behavior was not significantly altered under wide ranges in the values of the various parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Spruce budworm outbreaks are a natural pnenomenon associated with the vegetative climax of the spruce-fir forest (Blais 1952). Mature stands of balsam fir are one prerequisite for the development of these outbreaks, and, generally, it is only when this condition prevails over extensive areas that endemic populations of the insect become epidemic (Prebble and Morris 1951, Morris 1958). The destruction of a considerable amount of fir, and, to a lesser extent, white spruce and red spruce is a natural consequence of these outbreaks.…”
Section: Pouvait Varier Et Que Sur Un Total De 17 Intervalles Entre mentioning
confidence: 99%